2002
DOI: 10.1191/1362168802lr106oa
|View full text |Cite
|
Sign up to set email alerts
|

Autonomy and motivation: which comes first?

Abstract: When motivation has been discussed in relation to autonomy in language learning, it has often been put forward as a product of autonomy. This paper suggests a more complex relationship in which motivation in many cases precedes autonomy. It discusses some of the relevant literature and presents results from a large-scale study of Hong Kong tertiary students. The study aimed to assess students’ readiness for learner autonomy in language learning by examining their views of their responsibilities and those of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
169
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(188 citation statements)
references
References 13 publications
(10 reference statements)
15
169
2
2
Order By: Relevance
“…In other words, it can be concluded that evaluating the course is an important responsibility to be acquired in language learning. This result is also supported by the study of Spratt, Humphreys, and Chan (2002), in which "evaluating the course" is found significantly an important responsibility for the learners.…”
Section: The Relationship Between Gender and Learner Autonomysupporting
confidence: 74%
“…In other words, it can be concluded that evaluating the course is an important responsibility to be acquired in language learning. This result is also supported by the study of Spratt, Humphreys, and Chan (2002), in which "evaluating the course" is found significantly an important responsibility for the learners.…”
Section: The Relationship Between Gender and Learner Autonomysupporting
confidence: 74%
“…Dickinson, 1995;Spratt, Humphreys, & Chan, 2002;Ushioda, , 2003. While motivation is acknowledged to be one aspect of learner autonomy in Oxford's (2003) taxonomy, the types of motivation in play are not specified.…”
Section: A Proposed Construct Of Learner Autonomymentioning
confidence: 99%
“…These explanations may reflect the L2 speakers' attempts to minimize the gap between their ideal L2 self (i.e., a competent French speaker) and how the language switch encounter made them view their actual selves (i.e., a less than competent French speaker) (Dörnyei & Ushioda, 2009). The participants may have attributed the cause of the switch to an external catalyst rather than their own language skills in order to maintain a positive view of their actual selves and sustain their confidence to initiate future encounters in French (Pellegrino Aveni, 2007;Spratt, Humphreys, & Chan, 2002).…”
Section: Discussionmentioning
confidence: 99%